Pengaruh Implementasi Program Gerbang Mapan (Gerakan Pembangunan Masyarakat Pantai) Terhadap Pendapatan Masyarakat Di Desa Ketapang Kecamatan Mauk Kabupaten Tangerang - Silpiyah; Agus Sjafari; Agung Satrio Wicaksono (CV. Multi Kreasi Media, 2025)
The Gerbang Mapan program has been quite successful in its development, especially in the infrastructure sector, as its development has been evenly distributed due to its focus on planning. However, there are still many issues that have not been resolved. As a result of these issues, the Gerbang Mapan programme has not yet shown improvement in two main aspects, namely the economy and community empowerment. This study aims to determine the implementation level of the Gerbang Mapan programmeme, community income, and the programmeme’s impact on community income in Ketapang Village, Mauk Sub-district, Tangerang Regency. The research method used is quantitative. The sample consists of 98 respondents, with a purposive sampling technique employed. Data analysis in this study uses simple regression analysis with SPSS 26 software. The implementation of the Gerbang Mapan programme and community income in Ketapang Village, Mauk District, Tangerang Regency, are categorised as “very good,” with percentages of 83% and 75%, respectively. Based on the t-test, the calculated t-value is 3.618 with significance 0.000 < 0.05. This indicates a significant influence between the implementation of the Gerbang Mapan Programme and community income. The magnitude of the influence of the Gerbang Mapan Programme on community income in Ketapang Village, Mauk Subdistrict, Tangerang Regency, was found to be 12%, while the remaining 88% was influenced by factors outside the variables studied. It is recommended that the Tangerang Regency Government review and improve the implementation of the Gerbang Mapan Programme, particularly regarding funding and village management. To ensure the programme provides long-term economic benefits for coastal communities, funds must be distributed more effectively and sustainably.